Regional parliaments in network: towards a legislative federalism? - Seijas Villadangos, Esther (Journal of the Basque Parliament, 2020)
This essay studies how the interparliamentary collaboration and cooperation in a decentralized State, in particular the Autonomous State, has contributed to and can sustain the conformation of a solid, real substrate of a federal nature. The starting point will be the study of how such interparliamentary cooperation has been dealt with in Spain, in order to –without losing the benchmark of how interparliamentary cooperation has settled in a global order– refer, from a comparative point of view focused on the American and Canadian cases, how the parliaments in federal states have contributed to sustaining this territorial structure through their collaboration. Legislative federalism will be a final point, in which all the teachings of that previous case review will be summarized. An analysis of the achievements and challenges of interparliamentary cooperation will be the final reflection on the conception of interparliamentary territorial collaboration as a guarantee of pluralism and as a link between the unity and diversity that sustains the essence of a federation.